Germination of Mansonia altissima (A. Chev.) A. Chev. var. altissima: an endangered valuable timber species in Africa (Acta Scientiarum. Biological Sciences, 2020)
The in vitro seed germination which results in the production of disease-free seedlings and greenhouse germination of the seeds of Mansonia altissima was investigated in order to establish a better way of germination of the timber species. Five levels of GA3 treatment were used in in vitro germination with three replicate and two seeds were inoculated in each of the jam bottle. Whereas, in greenhouse germination, five levels of different treatments were used, replicated three times and each Petri plate contained 15 seeds. The experiment was repeated twice and the data from each experiment was put together and used for the statistical analysis. The results showed that seeds germination occurred eight days after inoculation in in vitro but in the case of greenhouse germination, it took only five days. For in vitro rapid germination of Mansonia altissima, the MS medium should be supplemented with 1.0 Î¼m of GA3. Equally, in greenhouse germination, the seeds need to be soaked in 1.0 mM of GA3 for 24 hours. Alternatively, in the absence of GA3, the seeds can be soaked in water for 24 hours before broadcasting the seeds on the seedbed for germination, as this will help to identify nonviable seeds.